Peran Legal Opinion Dalam Mencegah Risiko Hukum Pada Kontrak Kerja Sama - Siregar, M Sutan Muda; Sudirman, Maman (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In business practice, cooperation contracts are very important legal instruments for regulating the rights and obligations of the parties. However, careless drafting of contracts can lead to disputes due to vague clauses, clauses that conflict with regulations, or clauses that do not anticipate legal risks. One way to prevent such risks is through legal opinions, which are legal opinions prepared by lawyers or legal consultants to provide legal analysis, assess the compliance of contracts with applicable laws, and identify potential risks. This study uses a literature review method with a qualitative approach to analyze the mechanism of preparing legal opinions and their effectiveness in protecting the interests of the parties. The results show that the systematic and professional preparation of legal opinions can be a strategic instrument in preventing disputes, providing legal certainty, and helping the parties make safer decisions. However, legal opinions are not an absolute solution; their effectiveness depends on the quality of the analysis, the completeness of the data, and the professionalism and independence of the preparer, and must be combined with good risk management practices.